Warming Permafrost in the Western Alps: A Further Evidence of Elevation Dependent Warming? - Paolo Pogliotti; Edoardo Cremonese; Umberto Morra di Cella (Revue de Géographie Alpine)
The present study aims at characterising the recent thermal evolution of permafrost in the Aosta Valley region (Italy, Western European Alps) using active layer thickness anomalies and warming trends of both surface and deep temperatures as indicators. The dataset includes monitoring sites located at different altitudes and geomorphological contexts such as rock walls, high-altitude plateau and proglacial margins.The results show that the thickness of the active layer is increasing everywhere and that anomalies are consistent between sites despite their different characteristics and distances. Significant warming trends of about +0.2°C/10y are observed at 15 m depth in sites around 3000 m of elevation. In steep rockwalls warming trends at the rock surface are significant only on the north-facing faces where values are on average +0.42°C/10y at elevations above 4000 m.The present study aims to provide a snapshot on the current thermal evolution of permafrost in the north-western Alps as well as consistent and useful information for risk management. Taking advantage of this analysis, the study also aims to highlight as the temperature measures in permafrost could contribute to the elevation-dependent-warming debate.